Legal Analysis of Misyar Marriage According to the Views of Nashirudin Al Bani - Chaidir, Muhammad; Suparmin, Sudirman (Magister of Law, Faculty of Law, Universitas Islam Sultan Agung, 2024)
This study aims to examine the views of Nashirudin Al-Bani regarding Misyar marriage. In the perspective of Islamic Law, marriage is a very strong contract (mitsaqan ghalizhan), aimed at carrying out the commands of Allah SWT and is considered a form of worship. This research is empirical with a legal sociology approach, which analyzes the practice of Misyar marriage in the community through the perspective of Nashirudin Al-Bani. Primary data is obtained through interviews and observations of the Helvetia community, while secondary data is collected from various Islamic legal literature, books, journals, articles, and online searches. The results show that Misyar marriage is increasingly prevalent in several Muslim-majority countries, thus requiring a clear legal view. Misyar marriage is a form of marriage where couples live separately based on mutual agreement. Although husbands are still obliged to provide for their wives, these marriages are conducted with often hidden motives, which have the potential for negative repercussions. Nashirudin Al-Bani firmly forbids Misyar marriage, because he believes that this practice is close to adultery, opens opportunities for abuse of dowry, divorce, and remarriage without responsibility, and focuses more on fulfilling personal desires rather than moral and religious responsibilities.